Building on the past, shaping the future: The environmental mutagenesis and genomics society. (26th February 2013) - Wilson, Thomas E.; DeMarini, David M.; Dertinger, Stephen D.; Engelward, Bevin P.; Hanawalt, Philip C.; MacGregor, James T.; Smith‐Roe, Stephanie L.; Witt, Kristine L.; Yauk, Carole L.; Ljungman, Mats; Schwartz, Jeffrey L.; Klein, Catherine B.
<x xml:space="preserve">Abstract</x> In late 2012, the members of the Environmental Mutagen Society voted to change its name to the Environmental Mutagenesis and Genomics Society. Here, we describe the thought process that led to adoption of the new name, which both respects the rich history of a Society founded in 1969 and reflects the many advances in our understanding of the nature and breadth of gene‐environment interactions during the intervening 43 years. Environ. Mol. Mutagen. 54:153–157, 2013. © 2013 Wiley Periodicals, Inc.